Chemical Composition of Chlamydospores of Candida albicans - Jansons, Vilma K. (1970)
A variety of analytical techniques was employed to study the composition of the chlamydospore of Candida albicans. The outer, thin, electron-transparent layer was found to be composed of glucan, together with a small amount of chitin. The inner, thick, electron-dense layer is proteinaceous. The central structure is composed largely of ribonucleic acid and lipid globules. In addition to being acid-fast, the chlamydospore was found to contain glycolipids and to lose the property of acid-fastness on extraction with ethanol-ether.